Gender Differences in Online Behavior: Exploring the Moderating Effect on Loneliness and Cyberslacking among University Students - Rinaldi, Martaria Rizky; Aini, Luthfi Noor; Kurniawan, Aditya Putra (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2024)
Academic demands are capable of creating pressure, prompting students to find diversion through smartphone use and internet browsing. Unproductive internet use during learning is termed cyberslacking, a behavior known to be associated with loneliness. Therefore, this research aimed to explore the moderating role of gender in the relationship between loneliness and cyberslacking among university students. Using a quantitative correlational method, the investigation collected demographic data and adopted two scales, including the UCLA-3 Loneliness Scale and Cyberslacking Scale. Participants, comprising 226 students aged 18 to 25 years, were subjected to both descriptive and moderation analysis using Jamovi. The results showed that there was a significant influence of loneliness on cyberslacking, with gender identified as a moderator in such relationship. Recognizing gender differences in online behavior was crucial for enhancing the effectiveness of university policies and intervention strategies.